2021
DOI: 10.1097/mbc.0000000000001069
|View full text |Cite
|
Sign up to set email alerts
|

Thrombogenicity markers for early diagnosis and prognosis in COVID-19: a change from the current paradigm?

Abstract: Standard biomarkers have been widely used for COVID-19 diagnosis and prognosis. We hypothesize that thrombogenicity metrics measured by thromboelastography will provide better diagnostic and prognostic utility versus standard biomarkers in COVID-19 positive patients. In this observational prospective study, we included 119 hospitalized COVID-19 positive patients and 15 COVID-19 negative patients. On admission, we measured standard biomarkers and thrombogenicity using a novel thromboelastography assay (TEG-6s).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 17 publications
0
14
1
Order By: Relevance
“…The differences between thromboelastography parameters in patients who developed VTE and those who did not narrowed over time, likely due to the exclusion of measurements in patients who developed VTE and/or died over time; yet, lower MA, α, G, and clotting index were more common in patients who subsequently developed VTE compared with those who did not at nearly every timepoint. Prior retrospective studies have shown an association between hypercoagulable thromboelastography and the development of VTE; the differences between our results and those studies may be attributed to differences in methodology including retrospective study design selecting for patients with concern for coagulopathy and contributing to ascertainment bias, use of thromboelastography without heparinase or the TEG®6 machine, and use of the combined endpoints of VTE or death instead of controlling for the competing risk of death (5, 25–27).…”
Section: Discussioncontrasting
confidence: 77%
“…The differences between thromboelastography parameters in patients who developed VTE and those who did not narrowed over time, likely due to the exclusion of measurements in patients who developed VTE and/or died over time; yet, lower MA, α, G, and clotting index were more common in patients who subsequently developed VTE compared with those who did not at nearly every timepoint. Prior retrospective studies have shown an association between hypercoagulable thromboelastography and the development of VTE; the differences between our results and those studies may be attributed to differences in methodology including retrospective study design selecting for patients with concern for coagulopathy and contributing to ascertainment bias, use of thromboelastography without heparinase or the TEG®6 machine, and use of the combined endpoints of VTE or death instead of controlling for the competing risk of death (5, 25–27).…”
Section: Discussioncontrasting
confidence: 77%
“…Many other drugs targeting thrombosis are also being tested 19 . Techniques such as TEG, especially TEG6s, have proven useful in investigating the levels of thrombogenicity markers 139 and also evaluating the pharmacodynamic response to anticoagulants and aspirin in patients with COVID-19 (ref. 115 ).…”
Section: Investigating Platelets In Covid-19mentioning
confidence: 99%
“…[ 1 2 3 4 ] The COVID infection has been reported to have raised fibrinogen levels and hypercoagulable state in a recent study. [ 5 ]…”
Section: Discussionmentioning
confidence: 99%